Measuring the Impact of Regional Defense-Space Expenditures - Peterson, Richard S.; Tiebout, Charles M. (The Review of Economics and Statistics, 1964)
CONSIDERATIONS of the impact of changes in the volume and composition of expenditures by the defense and space agencies will be misleading if they ignore the regional component. In considering disarmament, traditional monetary and fiscal policy responses produce an effect which is nationwide in scope. Such policies may not be of much help to states and communities, such as California or Wichita, whose economies are heavily dependent upon defense expenditures. In addition, shifts in the regional pattern of these expenditures can produce similar stresses in local economies. A major problem in this connection has been the measurement of the defense-space expenditure impact in a region. Aside from an induced impact operating through regional consumption and business investment functions, the impact on income and employment can be divided into two components: (1) the direct impact through prime contract awards to firms, and (2) the indirect or inter-industry impact through subcontracts and purchases of supplies by prime contractors. While there have been some attempts to measure the direct impact, little work has been done which also accounts for the indirect impact. This paper reports on an effort to measure both the direct and indirect impact of defense-space expenditures on the manufacturing sector of the Los Angeles-Long Beach Standard Metropolitan Statistical Area (SMSA). The task is an empirical one. Hence, we shall briefly review some of the various techniques of measurement and present the results of a short-cut method to measure the impact on Los Angeles manufacturers. Empirical Difficulties Almost all approaches to the measurement of the regional impact of defense-space expenditure involve variations of an input-output framework.1 Unfortunately, given the present state of data availability, they are not operational, at least without extended research effort. National data from the 1947 table, while useful, are somewhat out of date.2 Regional data are all but nonexistent. Pending the development of more adequate data, some short cuts need to be examined. In the search for short cuts, it is useful to keep in mind what the gross flows data of an interregional input-output table reveal. Row information reflects where sales are made in terms of industries, final demand sectors, and regions. Column information indicates the source of inputs from other industries both inside and outside of the region. Short cuts, essentially, involve something less than the complete cross-check of independent estimates of the row and column entries. Most regional input-output studies, in fact, get these estimates sometimes from row information and sometimes from column information, but rarely from independent estimates of both. A column-oriented approach, which has a good deal of appeal, simply traces down the subcontractors. There is some evidence to suggest, as an order of magnitude, that half of a specific defense or space program prime contract is subcontracted.3 It would seem that tracing down a few layers of subcontractors would account for most of the impact. Unfortunately, this is not the case. When a prime